Peri‐implant bone organization surrounding zirconia‐microgrooved surfaces circularly polarized light and confocal laser scanning microscopy study. Issue 11 (21st August 2014) - Delgado‐Ruiz, Rafael Arcesio; Abboud, Marcus; Romanos, Georgios; Aguilar‐Salvatierra, Antonio; Gomez‐Moreno, Gerardo; Calvo‐Guirado, Jose Luis
Abstract Objectives To study the peri‐implant bone organization pattern of immediately loaded (IL) zirconia implants with microgrooved surfaces. Materials and Methods Forty‐eight dental implants of 4 mm diameter and 10 mm length were inserted after two months postextraction healing in the edentulous mandible of six dogs. Three groups of sixteen implants were used, titanium implants (Control), zirconia implants (test A), and zirconia‐microgrooved implants (test B), which were loaded immediately. After 4‐month healing period, implant–bone samples were processed and analyzed by circularly polarized light (CPL) and confocal laser scanning microscopy (CLSM) in two regions of interest ROI1 (to evaluate the interthread bone) and ROI2 (to evaluate the bone adjacent to the threads) of 1 mm thickness × 10 mm length each one. Results Bone organization differs near to the test B, compared with test A and control surfaces, active remodeling was detected surrounding test B implants, with alternancy of organized zones, meanwhile controls and test A areas showed organized areas mainly at 2 mm of implant surfaces. Transverse collagen fibers were significatively higher at ROI1 for test B implants (60.34 ± 4.34%), compared with controls (47.25 ± 3.51%) and test A (43.78 ± 2.78%) groups (P < 0.05). Meanwhile, it was not found any significant difference between groups in ROI2 (P > 0.05). CLSM confirmed the presence of collagen mineralized matrix inside microgrooves of test B groups. 3D reconstruction showed blood vessels in direct contact with the implant surfaces of all groups and bone and blood vessels penetration inside the microgrooves in test B group. Conclusion The organized pattern of the microgrooved surfaces is able to induce transverse collagen fiber microenvironment reaction to the load, being positive to promote and to maintain the bone remodeling; in addition blood vessels and bone cells are able to penetrate microgrooved surfaces.